Long Noncoding RNA MLK7-AS1 Promotes Non-Small-Cell Lung Cancer Migration and Invasion via the miR-375-3p/YWHAZ Axis - Jia, Jingzhou; Sun, Jiwei; Wang, Wenbo; Yong, Hongmei (Frontiers in Oncology, 2021)
Long noncoding RNAs act essential regulators in lung cancer tumorigenesis. Our research aimed to investigate the potential function and molecular mechanisms of MLK7-AS1 in NSCLC (non-small-cell lung cancer). QRT-PCR results indicated that the MLK7-AS1 expression level was upregulated in NSCLC cells and tissues. MLK7-AS1 strengthened cell migration and invasion in H1299 and A549 cells. Luciferase reporter assay found that MLK7-AS1 functioned as an endogenous sponge for miR-375-3p. Transwell assay results showed that miR-375-3p suppressed cell migration and invasion in H1299 and A549 cells. YWHAZ was confirmed as a target gene of miR-375-3p by Targetscan. YWHAZ overexpression promoted the invasion of H1299 and A549 cells. MLK7-AS1 upregulated YWHAZ expression and enhanced H1299 and A549 cell invasion by sponging miR-375-3p. MLK7-AS1 improved the metastasis ability of A549 in vivo. In conclusion, MLK7-AS1 was identified as a novel oncogenic RNA in NSCLC and can function as a potential therapeutic target for NSCLC treatment.